India's financial crisis and mounting public debt - Need to restore fiscal balance - Mathur, B.P. (2014)
Government has been financing its burgeoning public expenditure through fiscal deficits, which makes it vulnerable to economic and financial crisis. On an average, 35 per cent of public expenditure is met out of borrowed funds, bulk of which is on current consumption, as only one-third are used for income generating capital assets. This results in huge debt liability, with interest payments consuming more than one-third of revenue earned by the government. Government lacks the 'will' to raise taxes by taking hard and unpopular decisions. Tax revenue is financing only about 50 per cent of expenditure. There is no serious effort on the part of government to restrict public expenditure which is growing exponentially. Government's expenditure on salary and allowances of its employees has steeply increased as a result of Sixth Pay Commission award, which jumped from around 16 per cent to more than 25 per cent of its revenue earnings. There is also poor outcome of public expenditure due to outdated budgetary practices followed by government. Budgets should be approved for a three-year cycle and all unspent money should be allowed to be carried forward to the next year and the rule of lapse should be discarded. To put the economy on the path of prosperity, Government's foremost agenda should be freedom from crippling debt and restoring fiscal balance. - Reproduced.
Keywords: Fiscal policy - India; Public expenditure - India; Debt - India; Public debt - India; Economic recession - India; Economic recession